Photoactive metabolite mediated photodynamic therapy of Rhabdomyosarcoma cell lines using medicinal plants and Doxorubicin co-treatments - Sumbal Javaid; Irfan Zia Qureshi; Ahmat Khurshid; Tayyaba Afsar; Fohad Mabood Husain; Muhammad Khurshid; Janeen H. Trembley; Suhail Razak (BMC, 2024)
Abstract Background Medicinal plant-mediated combinational therapies have gained importance globally due to minimal side effects and enhanced treatment outcomes compared to single-drug modalities. We aimed to analyze the cytotoxic potential of each conventional treatment i.e., photodynamic therapy (PDT), chemotherapy (doxorubicin hydrochloride; Dox-HCl) with or without various concentrations of medicinal plant extracts (PE) on soft tissue cancer Rhabdomyosarcoma (RD) cell line. Methods The Rhabdomyosarcoma (RD) cell line was cultured and treated with Photosensitizer (Photosense (AlPc4)), Chemo (Dox-HCl), and their combinations with different concentrations of each plant extract i.e., Thuja occidentalis, Moringa oleifera, Solanum surattense. For the source of illumination, a Diode laser (λ = 630 nm ± 1 nm, Pmax = 1.5 mW) was used. Photosensitizer uptake time (∼ 45 min) was optimized through spectrophotometric measurements (absorption spectroscopy). Drug response of each treatment arm was assessed post 24 h of administration using 3-(4, 5-dimethyl-2-thiazolyl)-2, 5- 5-diphenyl-2 H- tetrazolium bromide (MTT) assay. Results PE-mediated Chemo-Photodynamic therapy (PDT) exhibited synergistic effects (CI < 1). Moreover, Rhabdomyosarcoma culture pretreated with various plant extracts for 24 h exhibited significant inhibition of cell viability however most effective outcomes were shown by low and high doses of Moringa oleifera compared to other plant extracts. Post low doses treated culture with all plant extracts followed by PDT came up with more effectiveness when compared to all di-therapy treatments. Conclusion The general outcome of this work shows that the ethanolic plant extracts (higher doses) promote the death of cancerous cells in a dose-dependent way and combining Dox-HCl and photo-mediated photodynamic therapy can yield better therapeutic outcomes.